Enhancing Community Reading Interest through Mentoring the Management of Batubasa Nagari Library - Manita, Rika Jufriazia; Wahyuni, Sri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This activity aims to increase community reading interest through mentoring the management of the Batubasa Nagari Library. The main focus of this program is to provide solutions to the low utilization of library facilities by the local community. The method used is a qualitative case study approach, with data collected through in-depth interviews, direct observation, and document analysis. The mentoring process involved intensive training for librarians on collection management, comprehensive collection audits, strategic planning for collection development, as well as collaboration with external parties and the implementation of information technology. The results of the activity showed that the mentoring successfully enhanced the skills of the library managers, improved collection management, and expanded community access to relevant reading materials. Additionally, the activity fostered close collaboration between library managers and the community, resulting in increased library visit frequency. In conclusion, mentoring the management of the Nagari library proved effective in enhancing reading interest through more professional management, the use of technology, and collaboration with various stakeholders. This strategy can be applied to other village libraries to support the improvement of community literacy